2021
DOI: 10.1002/ccd.29692
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and outcomes of acute kidney injury stratified by cardiogenic shock severity

Abstract: Background Acute kidney injury (AKI) is common among patients with cardiogenic shock (CS) and it is independently associated with mortality. We sought to assess the prevalence, severity, and prognosis of AKI as a function of cardiogenic shock severity in unselected Cardiac Intensive Care Unit (CICU) patients. Methods We retrospectively reviewed admissions to the Mayo Clinic between 2007 to 2015 and stratified patients by the AKI stage (based on modified Kidney Disease: Improving Global Outcomes criteria) and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…In the Mayo Clinic CICU cohort, age, the presence of systemic inflammatory response syndrome, acute kidney injury, and other noncardiac organ failure, severe acidosis, and echocardiographic findings were found to improve mortality risk stratification beyond SCAI SHOCK stages alone. [14][15][16][17][18] The importance of age as a risk factor for mortality, independent of shock stage, was likewise reported in CS cohorts. 4,7 Thayer et al and Garan et al showed the importance of pulmonary artery catheter use, congestion profile, and invasive hemodynamic data (particularly an elevated right atrial pressure) as risk modifiers independent of the shock stage in patients with CS.…”
Section: Studies Examining Risk Modifiers Within the Scai Shock Stage...mentioning
confidence: 74%
“…In the Mayo Clinic CICU cohort, age, the presence of systemic inflammatory response syndrome, acute kidney injury, and other noncardiac organ failure, severe acidosis, and echocardiographic findings were found to improve mortality risk stratification beyond SCAI SHOCK stages alone. [14][15][16][17][18] The importance of age as a risk factor for mortality, independent of shock stage, was likewise reported in CS cohorts. 4,7 Thayer et al and Garan et al showed the importance of pulmonary artery catheter use, congestion profile, and invasive hemodynamic data (particularly an elevated right atrial pressure) as risk modifiers independent of the shock stage in patients with CS.…”
Section: Studies Examining Risk Modifiers Within the Scai Shock Stage...mentioning
confidence: 74%
“…This is a common problem in clinical trials since patients with kidney disease are underrepresented ( 25 ). Even though acute and chronic kidney disease is present in 20–60% of patients with heart failure ( 26 28 ), patients with kidney disease are frequently excluded from trials ( 29 , 30 ). Many arguments exist for excluding these patients including the fact that prognosis of patients with kidney disease is significantly worse ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical information, vital signs, and laboratory data were extracted electronically from the medical record; admission laboratory values were defined as the first value after CICU admission or the values closest to CICU admission 9,11 . Data from the first 24 h of CICU admission were used to assign the Society for Cardiovascular Angiography and Intervention (SCAI) shock stage, but complete data to assign SCAI shock stage were only available for patients admitted from 2007 to 2015; because all patients had a diagnosis of CS, no patients were classified as SCAI shock stage A 2,11–17 . Echocardiographic variables were extracted electronically from a database for patients who had a transthoracic echocardiogram within one day before or after hospitalization 12 .…”
Section: Methodsmentioning
confidence: 99%